Derivadas PDF
Derivadas PDF
Derivadas PDF
Regras de Derivação
d d
c=0 (cf (x)) = cf 0 (x)
dx dx
d d
(f (x) + g(x)) = f 0 (x) + g 0 (x) f (g(x)) = f 0 (g(x))g 0 (x) (regra da cadeia)
dx dx
f 0 (x)g(x) − f (x)g 0 (x)
d d f (x)
(f (x)g(x)) = f 0 (x)g(x) + f (x)g 0 (x) (regra do produto) = (regra do quociente)
dx dx g(x) [g(x)]2
Tabela de Derivadas
d d
x=1 sech x = − tgh x sech x
dx d 1 dx
arcsen x = √
d n dx 1 − x2 d
x = nxn−1 cotgh x = − cossech2 x
dx d −1 dx
arccos x = √
d x dx 1 − x2
a = ax ln a d
dx d 1 csch x = − coth x cossech x
arctg x = dx
d loga e dx 1 + x2
loga x = d 1
dx x d −1 arcsinh x = √
arccotg x = dx x2 + 1
d dx 1 + x2
sen x = cos x
dx d 1 d 1
arcsec x = √ arccosh x = √
d dx |x| x2 − 1 dx x2 − 1
cos x = − sen x
dx d −1 d 1
arccosec x = √ arctanh x =
d dx |x| x2 − 1 dx 1 − x2
tg x = sec2 x
dx d d −1
d senh x = cosh x arcsech x = √
sec x = sec x tg x dx dx x 1 − x2
dx d
cosh x = senh x d 1
d dx arccoth x =
cotg x = − cosec2 x dx 1 − x2
dx d
d tgh x = sech2 x d −1
cosec x = − cosec x cotg x dx arccossech x = √
dx dx |x| 1 + x2
Identidades Trigonométricas
sen2 x + cos2 x = 1 sen(a − b) = sen a cos b − sen b cos a
Regra de Leibniz
d
Z v(x)
f (t)dt = f (v(x))v 0 (x) − f (u(x))u0 (x).
dx u(x)